Programmable sample and hold circuit for reconfigurable system / Nur Athirah Azman - Azman, Nur Athirah (2015)
This project presents a sample and hold circuit design with four different frequency applications such as biomedical signal ( 16Hz-10MHz), radio frequency ( <3kHz- 300GHz), intermediate frequency (l 10kHz-1500MHz) and power (35.9 kHz-90.6 kHz). The frequency applications will be the input to the sample and hold circuit of Silterra CMOS O. l 3 µm technology. The designed sample and hold circuit use 1.5V for the power supply and designed using Mentor Graphic tools. Total power dissipation for sample and hold circuit is 153 .89µ Watts. The variety of frequency applications was used to obtain the different output signal for sample and hold circuit design before the signal is sent to the other system such as an analog digital converter